2012
DOI: 10.1089/hum.2011.030
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Anti-Inflammatory and Anti-Angiogenic DNA Vaccination on Diabetic Nephropathy in Rats

Abstract: Inflammation and angiogenesis play a crucial role in the pathomechanism of diabetic nephropathy. Monocyte chemoattractant protein 1 (MCP) is a key regulator of the immune system in kidneys, and its inhibition with a dominant-negative mutant lacking the N-terminal amino acids 2-8 (7ND) reduces renal fibrosis. Angiomotin (Amot) is a novel angiogenesis modulator. We studied the effects of inhibition of Amot and MCP using DNA vaccination on incipient diabetic nephropathy in rats. Plasmid DNA (with either 7ND or hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 67 publications
(68 reference statements)
0
9
0
Order By: Relevance
“…Several studies have reported an increase in potent stimulators of angiogenesis in diabetic nephropathy [ 41 , 42 ]. In addition, the therapeutic efficacies of anti–angiogenic strategies have further demonstrated the involvement of angiogenesis in the progression of diabetic nephropathy [ 13 , 43 ]. In this context, genetics of inflammatory cytokines and angiogenesis is important to analyze the involved genes and their role in susceptibility to diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported an increase in potent stimulators of angiogenesis in diabetic nephropathy [ 41 , 42 ]. In addition, the therapeutic efficacies of anti–angiogenic strategies have further demonstrated the involvement of angiogenesis in the progression of diabetic nephropathy [ 13 , 43 ]. In this context, genetics of inflammatory cytokines and angiogenesis is important to analyze the involved genes and their role in susceptibility to diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Chen and Ziyadeh, [ 12 ] reported attenuation of diabetic albuminaria by blockade of VEGF signaling pathway. Further, a recent study showed anti-angiogenic and anti-inflammatory DNA vaccination ameliorates the progression of glomerular pathology in an animal model of diabetic nephropathy [ 13 ]. As inflammation and angiogenesis play a crucial role in the pathomechanism of diabetic nephropathy, many studies have investigated the association of genetic polymorphism in these pathway genes with the risk of diabetic nephropathy.…”
Section: Introductionmentioning
confidence: 99%
“…Proteinuria was analyzed by the pyrogallol red method ( 34 ). 10 µL of samples were mixed with 300 µL of pyrogallol red reagent (composed from pyrogallol red, methanol, succinic acid, sodium oxalate, sodium benzoate, disodium molybdate, sodium dodecyl sulfate, and Brij 35).…”
Section: Methodsmentioning
confidence: 99%
“…Creatinine in urine was assessed by Jaffe method, adding NaOH and picric acid (ratio 5:1) to the samples and measuring the absorbance at 492 nm (25). The concentration of urinary proteins was measured by the pyrogallol red-molybdate method, reading the absorbance at 592 nm (26).…”
Section: Kidney Functionmentioning
confidence: 99%